1988
DOI: 10.1136/oem.45.4.209
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of cancer among welders, platers, machinists, and pipe fitters in shipyards and machine shops.

Abstract: The incidence of cancer in 12 693 shipyard and machine shop male workers (1689 welders, 4308 platers, 6003 machinists, 693 pipe fitters) employed for at least one year between 1945 and 1960 was investigated in a retrospective cohort study. The welders had welded only mild steel and had not been exposed to hexavalent chromium containing fume. The follow up was 99-7% complete and the total number of person-years was 304 682. The incidence of cancer in 1953-81 was ascertained through the Finnish Cancer Registry. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
27
1

Year Published

1989
1989
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 21 publications
6
27
1
Order By: Relevance
“…The demonstration of an increased incidence of lung cancer in several occupational categories at the shipyard is in accordance with the results of other investigations (9,17,18,20,21). However, the results from these studies are inconsistent as to which occupational groups had an excess of asbestos-related cancers, probably due to diverse routines for asbestos handling or possibly to methodological shortcomings.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…The demonstration of an increased incidence of lung cancer in several occupational categories at the shipyard is in accordance with the results of other investigations (9,17,18,20,21). However, the results from these studies are inconsistent as to which occupational groups had an excess of asbestos-related cancers, probably due to diverse routines for asbestos handling or possibly to methodological shortcomings.…”
Section: Discussionsupporting
confidence: 81%
“…The magnitude of the excess was higher than that reported in some epidemiologic studies on shipyard employees (9,17,20), while other authors have demonstrated an approximately twofold risk of lung cancer for shipyard workers (19,21,22).…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…Due to the fact that five of these subcohorts (ie, Finland, France, Germany, Norway, Sweden) had been separately published or updated (26,(32)(33)(34)(35), the IARC study itself was excluded from the database of the metaanalysis. However, in order to avoid losing the information provided by the four other unpublished subcohorts (ie, Denmark, England, Italy, Scotland), we extracted the relevant data on these subcohorts from the IARC study report (30) and included them in the database.…”
Section: Ambroise Et Almentioning
confidence: 99%